Klaszter-analízis a baromfihús-termékek piacán - Vincze-Lendvai, Edina (Jelenkori Társadalmi és Gazdasági Folyamatok, 2007)
The products of the poultry species play a more important role in the supply with food of the population of Earth. In our research we made a representative 1000-persons- questionnaire fact-finding. We wanted to take the measure of consumers’ attitudes about processed poultry products. After the apprehension of the answers we made factor- and cluster-analysis. The 97,6 percents of the poultry-products consumers was divided into 7 factors and 4 clusters respectively by the factor- and cluster-analysis based on the life-style, the demography and the attitudes. The most substantial factor is the price for the members of the "A" cluster, and the quality for the people of the "B". Persons belong to "C" cluster like the branded, convenience products, and the moneyless pensioners from "D" think the most important factor is the price.